(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
The powder metallurgical process has the distinctive advantage of near net shape manufacturing, getting rid of finished machining processes and hence material wastage. Mechanical alloys mix part of metal powder into a powder metallurgical route to create alloys very similar to historically developed alloys. Mechanical alloys are the sound alloying process. Metal powders are mixed to create a consistent delivery before compaction with the aid of ball mill. The composites of the hybrid metal matrix have two separate secondary phases founded in the primary phase, that demonstrate an intriguing behavior and are worth studying in the field of composite science. In this study, various previous studies on mechanical alloy of aluminum with different components and metals are reviewed and their findings are illustrated, in contrast with conventional alloys.